Design and Presentation of Professional Ethics Criteria and Indicators for the Promotion of Political Accountability within Iranian’s Government Organizations (Case Study: National Chief Executive Devices) - Asfestani, Rasool Sarihi; Peykani, Mehraban Hadi; Etebaryan, Akbar (International Review of Management and Marketing, 2017)
Today, professional ethics has gained a strategic position in the global environment due to intertwined professions and many challenges arising from globalization and also provides wide range of knowledge in which its alignment with political accountability could facilitates achievement of higher goals and objectives and specificly may strengthen the relationship of original-lawyer between citizens and authorities, reduce corruption, increase the legitimacy of the political system. In this study, we have formulated a framework by reviewing the literature and related researches so that with application of quality and quantitative combinatory approch as well as utilization of Delphi and judgmental sampling and chain and professional acceptance of scientific and organizational model (32 members), a comporehensive model was instituted in the form of a standard model (individual, organizational and cross- organizational) and 23 indicators of professional ethics to promote political accountability. Then, realized model structures in the studied organizations has been tested through structural equation modeling (confirmatory factor analysis) using smart PLS software.Meanwhile, Cronbach’s alpha (0.965) is used to measure questionnaire’s reliability in addition to evaluation of validity. Moreover, among national executive accountability, 124 members are selected for this study through Morgan table and stratified random sampling method so that the situation of each dimensions such as individual (3.258), organizational (3.727) and cross-organizational (3.478) are obtained unfavorably. Overall, this study defines a new method to analyze and measurements of enhance public accountability and professional ethics under Iranian’s government agencies. Keywords: Ethical Accountability, Political Accountability, Organizational professional Ethics, Environmental professional ethics JEL Classifications: C53, C5, E37, E32